Chronic Metabolic Acidosis in Chronic Kidney Disease - Daniel Patschan; Susann Patschan; Oliver Ritter (Karger Publishers, 2020)
Background: Metabolic acidosis may be diagnosed as chronic (cMA) if it persists for at least 5 days, although an exact definition has not been provided by any guidelines yet. The most common cause is CKD; numerous less-known diseases can also account for cMA. Summary: In recent years, CKD-associated cMA has been proposed to induce several clinical complications. The aim of the article was to assess the current clinical evidence for complications and the respective management of CKD-associated cMA. In summary, cMA in CKD most likely promotes protein degradation and loss of bone mineral density. It aggravates CKD progression as indicated by experimental and (partly) clinical data. Therefore, cMA control must be recommended. Besides oral bicarbonate, dietary interventions potentially offer an alternative. Veverimer is a future option for cMA control; further systematic data are needed. Conclusions:The most common cause of cMA is CKD. CKD-associated cMA most likely induces a negative protein balance; the exact role on bone metabolism remains uncertain. It presumably aggravates CKD progression. cMA control is recommendable; the serum bicarbonate target level should range around 24 mEq/L. Veverimer may be established as future option for cMA control; further systematic data are needed.